Insulation failure mapping on power transformer bushing using FRA and electrostatic simulation - Salem Mgammal Al-Ameri; Waleed M. Hamanah; Ali Ahmed Salem; Mohd Fairouz Yousof; Samir Ahmed Al-Gailani; A. Abu-Siada (PLoS ONE, 2026)
The power transformer bushing is a critical insulation component and a frequent contributor to transformer failures. This paper presents combined electrical and Multiphysics approaches for mapping failure mechanisms in Resin-Impregnated Paper (RIP) transformer bushings using frequency response analysis (FRA) and electrostatic analysis. An 11 kV/0.433 kV, 500 kVA power transformer bushing is selected as a case study and modeled using a MATLAB-based equivalent circuit to simulate its FRA characteristics. Variations in bushing circuit capacitance are introduced to represent insulation degradation, surface pollution, and insulator damage, and the corresponding failure modes are mapped through their distinctive FRA signatures. To provide physical insight into these failure mechanisms, a detailed model is developed in COMSOL Multiphysics, where degradation, pollution, and destructive damage are analyzed using electric field and electric potential distributions. The results from the FRA simulation and electrical Multiphysics in this paper provide a framework for understanding the behavior of transformer bushing failures and enable early fault detection. This also improves the transformer bushing maintenance and condition monitoring.